CRISPR‐Cas13d effectively targets SARS‐CoV‐2 variants, including Delta and Omicron, and inhibits viral infection. Issue 1 (31st January 2023) - Liu, Zongzhi; Gao, Xiang; Kan, Chuanwen; Li, Lingyu; Zhang, Yuan; Gao, Yibo; Zhang, Shengyuan; Zhou, Liangji; Zhao, Hui; Li, Mingkun; Zhang, Zheng; Sun, Yingli
Abstract: The recent pandemic of variants of concern (VOC) of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) highlights the need for innovative anti‐SARS‐CoV‐2 approaches in addition to vaccines and antiviral therapeutics. Here, we demonstrate that a CRISPR‐Cas13‐based strategy against SARS‐CoV‐2 can effectively degrade viral RNA. First, we conducted a cytological infection experiment, screened CRISPR‐associated RNAs (crRNAs) targeting conserved regions of viruses, and used an in vitro system to validate functional crRNAs. Reprogrammed Cas13d effectors targeting NSP13, NSP14, and nucleocapsid transcripts achieved >99% silencing efficiency in human cells which are infected with coronavirus 2, including the emerging variants in the last 2 years, B.1, B.1.1.7 (Alpha), D614G B.1.351 (Beta), and B.1.617 (Delta). Furthermore, we conducted bioinformatics data analysis. We collected the sequence information of COVID‐19 and its variants from China, and phylogenetic analysis revealed that these crRNA oligos could target almost 100% of the SARS‐CoV family, including the emerging new variant, Omicron. The reprogrammed Cas13d exhibited high specificity, efficiency, and rapid deployment properties; therefore, it is promising for antiviral drug development. This system could possibly be used to protect against unexpected SARS‐CoV‐2 variants carrying multiple mutations. Abstract : Cas13d‐crRNAs inhibit both ancestral and mutated SARS‐CoV‐2 replication. Cas13d‐crRNAs inhibit both ancestral and mutated SARS‐CoV‐2 replication including Delta. Cas13d‐crRNAs could inhibit Omicron and other SARS family strains and are a potential pan‐SARS inhibition strategy.